Demanda laboral del profesional en periodismo en los medios nacionales - Bonilla Granda, José Vladimir (2019)
When starting a university career, when starting a university career the aspirants have a perspective of the possible places of employment and even of means of communication according to the interest of the same, some are directed according to their taste, be it sport, politics, community or specialty subjects. During the course of the university career, the students manage to clear doubts and even acquire and define their professional personality, and try to open their way to gain experience by accessing a job in a media outlet………